Interleukin-2 Therapy Induces CD4 Downregulation, Which Decreases Circulating CD4 T Cell Counts, in African Green Monkeys - Mudd, Joseph C. (J Virol, 2016)
African green monkeys (AGMs) are natural hosts of simian immunodeficiency virus (SIV(AGM)). Because these animals do not develop simian AIDS despite maintaining high viral loads, there is considerable interest in determining how these animals have evolved to avoid SIV disease progression. Unlike nonnatural hosts of SIV, adult AGMs maintain low levels of CD4(+) T cells at steady states and also have a large population of virus-resistant CD8αα T cells that lack CD4 expression despite maintaining T helper cell functionalities. In recent work, we have shown that homeostatic cytokines can induce CD4 downregulation in AGM T cells in vitro. Through administering therapeutic doses of recombinant human interleukin-2 (IL-2) to AGMs, we show here that this mechanism is operative in vivo. IL-2 therapy induced transient yet robust proliferation in all major T cell subsets. Within the CD4(+) T cell population, those that were induced into cycle by IL-2 exhibited characteristics of CD4-to-CD8αα conversion. In all animals receiving IL-2, circulating CD4(+) T cell counts and proportions tended to be lower and CD4(−) CD8αα(+) T cell counts tended to be higher. Despite reductions in circulating target cells, the viral load was unaffected over the course of study. IMPORTANCE The data in this study identify that homeostatic cytokines can downregulate CD4 in vivo and, when given therapeutically, can induce AGMs to sustain very low levels of circulating CD4(+) T cells without showing signs of immunodeficiency.